COGENT: evaluating the consistency of gene co-expression networks - Bozhilova, LV; Pardo-Diaz, J; Reinert, G; Deane, CM (Oxford University Press, 2020)
Gene co-expression networks can be constructed in multiple different ways, both in the use of different measures of co-expression, and in the thresholds applied to the calculated co-expression values, from any given dataset. It is often not clear which co-expression network construction method should be preferred. COGENT provides a set of tools designed to aid the choice of network construction method without the need for any external validation data.